Dengue Deaths: Associated Factors and Length of Hospital Stay. (4th July 2016) - Pooransingh, S.; Teelucksingh, S.; Dialsingh, I.
Abstract : Background . Dengue continues to pose a public health problem globally. Objective . To review factors associated with patients who died from dengue in Trinidad. Methods . A retrospective case note review of hospitalized patients who died during 2001 to 2010. Results . A total of 23 cases were identified: 13 males, 10 females—12 East Indians, 9 Africans, and 2 unknown. More than half (n = 17 ) were over 40 years of age with 10 being over 60 years of age; three were children. A falling platelet count was observed in 16 while 18 patients had a low normal haematocrit. There was a significant association of ethnicity, hypertension, and diabetes with length of hospital stay. Conclusions . The study sample included 10 patients over 60 years of age. Patients with diabetes and hypertension and patients of East Indian origin appeared to have a shorter hospital stay prior to death.